Analisis Dampak Kecerdasan Buatan (AI) terhadap Kepuasan dan Kepercayaan Pelanggan Asuransi Syariah di Era Digital: Peran Moderasi Literasi Digital - Amrullah; Huda, Nurul (ITB AAS INDONESIA Surakarta, 2025)
This study aims to analyze the impact of Artificial Intelligence (AI) implementation on customer satisfaction and trust in the Islamic insurance industry in the digital era, while also examining the moderating role of digital literacy. Using a quantitative approach with an explanatory and cross-sectional survey design, the research involved 200 Islamic insurance customers in the Greater Jakarta area selected through purposive sampling. The study focused on evaluating the influence of AI features such as chatbots, automated claim processes, and service personalization on customer perceptions. Data were collected through an online questionnaire and analyzed using SPSS version 25 with multiple linear regression and moderated regression analysis (MRA). The results indicate that AI has a positive and significant impact on both customer satisfaction and trust. Furthermore, digital literacy significantly moderates these relationships. These findings highlight that the effectiveness of AI implementation is greatly influenced by customers’ digital literacy and alignment with Sharia principles. This research contributes empirically to filling the gap in literature on Islamic financial technology and offers practical implications for developing ethical and inclusive AI-driven digital service strategies.